Community-acquired methicillin-resistant Staphylococcus aureus invasive infections: a case series from Central-South Chile - Aguayo-Reyes, Alejandro; Morales-León, Felipe; Quezada-Aguiluz, Mario; Quezada, Martha; Mella, Sergio; Riedel, Gisela; Herrera-Chávez, Néstor; Espine, Yohana; González-Rocha, Gerardo; Opazo-Capurro, Andrés (Frontiers in Medicine, 2024)
The emergence of community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) infections at the end of the 20th century represents a significant shift in the epidemiology of staphylococcal infections and, consequently, their clinical management. There are diverse CA-MRSA clones that are widely spread worldwide, showing differences in their regional dissemination, which has been dynamically changing over time. Although the first CA-MRSA description occurred about 30 years ago, its epidemiology in certain regions, such as South America, has been poorly explored, resulting in a gap in the understanding of the epidemiology of CA-MRSA in under-represented countries/regions. This report describes the first four clinical cases of invasive infections caused by CA-MRSA in a tertiary hospital in the central-southern region of Chile. It also associates the clinical characteristics of the infections with the microbiological and molecular features of the isolates. The four S. aureus isolates belong to sequence type 8, which has been widely described as a cause of community-acquired infections. All of them presented a wide resistome and virulome. Additionally, in two of them, it was possible to reconstruct the COMER genetic element, present in the USA300-Latin American variant clone.Considering these findings, it is crucial to prepare for a potential increase in invasive CA-MRSA infections in Chile. This would involve enhancing current surveillance systems and maintaining a low threshold of suspicion for these infections among clinicians.